Investigasi Lingkungan Pengendapan berdasarkan Fasies Batuan Karbonat Formasi Pamutuan Daerah Sindangsari dan Sekitarnya, Cimerak, Pangandaran, Provinsi Jawa Barat - Fistina Audrey, Vivi; Rizqi, Al Hussein Flowers; Kurniawan, Sandi; Wijaya, Naufal Arya; Sugarbo, Oky (ReTII, 2023)
The research area is in the Sindangsari and surrounding areas, Cimerak District, Pangandaran Regency, West Java Province. The study area is included in the Pamutuan Formation, which is exposed in the South of the Karangnunggal map sheet, the Middle Miocene Pamutuan Formation, with a shallow marine depositional environment. Differences in sedimentation processes and the relationship between formations at several locations are thought to be due to the influence of early paleogeography. This is an interesting study because it can provide a specific description of the development of the depositional environment in the study area. In order to understand the Pamutuan Formation's sedimentation process, facies and depositional environment analyses were carried out in this study. The method used in this study included collecting data by selecting representative samples and carrying out petrological and petrographic descriptions to determine a facies such as lithology. Based on data analysis, four rock facies were obtained; Greywacke lithic and Mudrock, Bounstone, facies Packstone, and Mudstone. These facies were deposited in four alternating depositional environments: sand shoals, reef margin, slope, and toe of the slope. Microfossil analysis shows that carbonate rocks from the Pamutuan Formation in the study area were deposited at N 13 – N 14 (Middle Miocene) in the Middle Neritic – Outer Neritic environment (100 – 200 meters). Keyword : facies, depositional environment, pamutuan, Southern mountain, pangandaran.